The scope of alternatives: indefiniteness and islands. - Charlow, Simon (Linguistics & Philosophy, 2020)
I argue that alternative-denoting expressions interact with their semantic context by taking scope. With an empirical focus on indefinites in English, I show how this approach improves on standard alternative-semantic architectures that use point-wise composition to subvert islands, as well as on in situ approaches to indefinites more generally. Unlike grammars based on point-wise composition, scope-based alternative management is thoroughly categorematic, doesn't under-generate readings when multiple sources of alternatives occur on an island, and is compatible with standard treatments of binding. Unlike all in situ (pseudo-scope) treatments of indefinites, relying on a true scope mechanism prevents over-generation when an operator binds into an indefinite. My account relies only on function application, some mechanism for scope-taking, and two freely-applying type-shifters: the first is Karttunen's (Linguist Philos 1(1):3–44, 1977. 10.1007/BF00351935) proto-question operator, aka Partee's (in: Groenendijk, de Jongh, Stokhof (eds) Studies in discourse representation theory and the theory of generalized quantifiers, Foris, Dordrecht, 1986) IDENT, and the second can be factored out of extant approaches to the semantics of questions in the tradition of Karttunen (1977). These type-shifters form a decomposition of LIFT, the familiar function mapping values into scope-takers. Exceptional scope of alternative-generating expressions arises via (snowballing) scopal pied-piping: indefinites take scope over their island, which then itself takes scope.